El uso de antibióticos y su resistencia microbiana: Impacto en la producción avícola y la salud pública (2024)
By 2028, it is estimated that meat production in the poultry sector could reach 141 million tons. In order to meet this goal, many producers have opted for methods that optimize poultry house space and the time needed to keep them in the right conditions for consumption, which has led to an increase in diseases and, consequently, the inappropriate use of antibiotics. Therefore, the objective of this research was to carry out a systematic literature review to compile the existing information on the use of antibiotics in poultry production and the impact that this use generates on poultry production and public health. To meet this objective, the analysis focuses on the consequences of the inappropriate use of antibiotics in poultry production and antibiotic resistance in animals and humans. The methodology used was the PRISMA model (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) by establishing a search method in databases such as: ScienceDirect, Google Scholar and Pub Med using Boolean operators such as "AND" and "NOT" considering inclusion and exclusion criteria, filtering mainly the years of publication, languages and subject matter in accordance with the objective of the review. The final selection of the literature review includes 47 articles from which it was inferred that poultry production has a great responsibility on public health, since this production, being the most demanded and affordable, implements antibiotics as growth promoters to enhance its productive results, but at the same time it generates consequences on animal and human health. Keywords: